Intraluminal Epidermal Growth Factor Affects Growth of N‐Methyl‐N‐nitrosourea‐initiated Rat Bladder Carcinoma - Kawai, Koji (Jpn J Cancer Res, 1995)
To confirm our recent finding that epidermal growth factor (EGF) appeared to contribute to the tumor‐enhancing effect demonstrated by normal rat urine, we conducted 2 experiments using our heterotopically transplanted rat urinary bladder model. In experiment 1, after a single dose (0.25 mg) of N‐methyl‐N‐nitrosourea (MNU), we intravesically administered EGF (0.5 ml of 500 ng/ml phosphate‐buffered saline) once a week for 30 weeks. Instillation of EGF induced a significantly larger number of tumors than did instillation of the vehicle (P=0.03). EGF without MNU initiation did not induce tumors. In experiment 2, 2 groups received instillation of killed Escherichia coli (5 × 10(8) cells)/0.5 ml phosphate‐buffered saline once a week for 4 weeks to expand the MNU‐initiated cell population. Subsequent EGF treatment significantly increased the incidence of tumors (P=0.01). In the groups which did not receive killed E. coli, EGF treatment induced a significantly higher number of tumors than did vehicle treatment (P<0.001). All of the tumors were low‐grade, superficial transitional cell carcinomas. These observations indicate that EGF acts as a growth‐stimulating factor on dormant neoplastic cells and thereby increases the number of tumors.